Pricing strategies in the Malaysian manufacturing sector : a qualitative study - Tan, Derrick Xue Fei (2018)
To keep up with the challenges of ever-increasing globalisation, Malaysian government is targeted to upgrade its value chain of the manufacturing sector to high value-added and complex products. A way to accelerate the transformation is to collaborate closely with world-class multinational industrial supplier to enhance the technological acquisition and increase productivity of the local manufacturers. However, many multinational industrial suppliers were found to be struggled in mastering the pricing strategy in emerging market such as Malaysia, with intense competition from other MNCs competing in premium niches and local lower cost giants in middle and low market segments. Under such circumstances, the only way to sustain the business is through strategic implementation of customer value-based pricing. The present study is aimed to investigate the unique needs and preferences of four selected heavy industries in Malaysia – cement, steel, oil and gas, and power generation. Through in-depth interviews with eleven senior managers from the local heavy industries and nine senior managers from the existing multinational industrial suppliers, the results indicated that there is a gap of understanding between the buyers’ expectations and suppliers’ price and product offerings. Specific customer economic values and unique buying behaviours of each industry were identified, allowing the multinational suppliers to formulate effective pricing strategies around these local values to maximise the profits. The study contributes to the literature in discovering the customer economic values, and implementation of strategic pricing in Malaysian manufacturing sector, an area which unexplored previously.